School Principals’ Opinions on Autonomy in School Administration - İbrahim Limon; Bahri Aydın (Sakarya University Journal of Education)
This study aims to determine school principals’ views on autonomy in school administration. Phenomenological design was employed in the study. Data were collected through interviews and analyzed using descriptive analysis. The participants were 14 high school principals. They were employed by maximum diversity sampling method. Data was collected through a semi-structured interview form. Accroding to findings, all of the participants stated that a school principal should be autonomous in performance evaluation, budget management, deciding on expenditures. On the other hand, most of them stated that a school principal should be autonomous in selecting deputy principal and the staff, deciding workday calendar and daily timetable, coursebooks and syllabus, quota of the school and the number of the students for each classroom. Another finding of this study is that local governments and parents are the most important components that support an autonomous school principal. As for the advantages and disadvantages of principal autonomy it is stated that the educational quality and efficacy of school administration will increase and the student performance will improve; however, there may be subjective practices and pressures on school principal. Lastly, political power and centralized educational system are regarded as the barriers to principal autonomy.